The observed disposition by small, medium and micro enterprises on incubated business support in South Africa - Barnes, Brendan Clive (My University, 2018)
South Africa is a country facing many economic challenges. The three most urgent remain the alleviation of poverty, the creation of equal opportunities and the achievement of economic growth and prosperity. A vehicle which has been identified to address such challenges is Small, Medium and Micro Enterprise (SMME) development, specifically an initiative known as business incubation. Incubated business support programs are considered highly influential in accelerating the creation of successful entrepreneurial ventures. However, some studies reveal entrepreneurs/SMMEs perceive little to no value in such programs suggesting that these initiatives are poorly marketed and ineffectively implemented. This research intended to provide an insightful view of incubated business support programs from the entrepreneur/SMME perspective. The research was carried out primarily in the Gauteng Province. Data collection was in the form of a questionnaire distributed through a web based survey tool called Qualtrics. A total of 334 research questionnaires were sent out, 75 were returned and identified as useful. The accompanying email contained a link to the questionnaire and a covering letter explaining the purpose, objectives and nature of the survey. The letter also assured the respondents of their privacy and anonymity. The respondents were perceived to have a high willingness to participate in incubated business support programs which suggested that they understood and appreciated the importance and effectiveness of these programs on nascent firms. However, the study revealed little on the association between the demographics of respondents and which services were offered by incubators. The findings of the research will benefit different stakeholders that have an interest in understanding the South African SMME environment as well as business incubation. Understanding incubated business support programs, from the entrepreneurial perspective, provides important information for such programs to be better designed and increase the effectiveness of their implementation in South Africa
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2018